Comparative Analysis of Learning Outcomes Between Conventional and Google Classroom-Assisted Learning at Vocational High School - Rievaldy Handhianto; Zulia Chasanah; Abdul Ngafif (Jurnal Studi Guru dan Pembelajaran, 2026)
The urgency in this study lies in how student learning outcomes are influenced by the use of the digital application Google Classroom during the learning process. This study aimed to compare students’ learning outcomes between conventional learning and Google Classroom–assisted learning in a Vocational High School context. A quantitative approach employing a quasi-experimental non-equivalent control group design was used. The participants consisted of 45 tenth-grade students at SMK YPT Purworejo, Central Java, Indonesia, selected through purposive sampling. One class served as the experimental group receiving instruction through Google Classroom, while the other class was taught using conventional learning methods. Students’ learning outcomes were measured using a post-test achievement test. The data were analyzed using descriptive statistics, assumption testing, the Mann–Whitney U test, and effect size analysis. The results indicated that students in the Google Classroom–assisted learning group achieved higher mean scores than those in the conventional learning group. The Mann–Whitney U test revealed a marginally significant difference between the two groups (p = .050). Furthermore, the effect size analysis indicated a moderate effect (r = 0.29), suggesting meaningful practical value. Overall, the findings indicate that Google Classroom–assisted learning tends to support better learning outcomes than conventional learning in Vocational High Schools, although its effectiveness depends largely on pedagogical integration rather than technology use alone.